Caracterização e propriedades mecânicas de uma lima rotatória de NiTi fabricada através de torção - Vieira, Victor Talarico Leal (2010)
The aim of this study was to characterize the TF® instrument of different tapers using the stereo and the electronic microscopy and to measure the proprieties of flexibility and microhardness Vickers. All the tapers of TF® files was used: 0,04; 0,06; 0,08 e 0,10 mm/mm. The stereomicroscopy associated with the AxioVision® program was used to verify: the tip angle, the helical angle, the taper and the tip diameter of the instruments. The scanning electronic microscopy was used to check possible defects of machining and finishing at the surface. The flexibility and the microhardness were measured with the bending and microhardness Vickers tests. About the micromorfology of the TF® instruments it was possible to conclude that the manufacturer attended the values espoused by the standard number 28 of ANSI/ADA. The scanning electronic microscopy showed many important defects of finishing surface and distortion on the instrument helical. The instrument flexibility change with the taper. The forces to induct the phase transformation by stress on the TF® instruments with taper 0,06; 0,08 e 0,10 mm/mm was respectively 100gf, 150 gf and 250 gf. The values of microhardness Vickers of the TF® instruments are compatible with the rotary instruments manufactured by the machining process.